1998
DOI: 10.1002/pro.5560071108
|View full text |Cite
|
Sign up to set email alerts
|

Toward a universal inhibitor of retroviral proteases: Comparative analysis of the interactions of LP‐130 complexed with proteases from HIV‐1, FIV, and EIAV

Abstract: One of the major problems encountered in antiviral therapy against AIDS is the emergence of viral variants that exhibit drug resistance. The sequences of proteases (PRs) from related retroviruses sometimes include, at structurally equivalent positions, amino acids identical to those found in drug-resistant forms of HIV-1 PR. The statine-based inhibitor LP-130 was found to be a universal, nanomolar-range inhibitor against all tested retroviral PRs. We solved the crystal structures of LP-130 in complex with retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 37 publications
0
36
0
Order By: Relevance
“…It has been shown that inhibitors of the catalytic function or reactivity associated with a protein fold effective across species are not likely to elicit drug resistance by amino acid mutation (26). Thus, because dehydrons are highly conserved and promoters of interactions (3), it makes sense that ''universal inhibitors'' (i.e., those effective across species and not eliciting drug resistance) should be designed precisely to wrap such dehydrons.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that inhibitors of the catalytic function or reactivity associated with a protein fold effective across species are not likely to elicit drug resistance by amino acid mutation (26). Thus, because dehydrons are highly conserved and promoters of interactions (3), it makes sense that ''universal inhibitors'' (i.e., those effective across species and not eliciting drug resistance) should be designed precisely to wrap such dehydrons.…”
Section: Discussionmentioning
confidence: 99%
“…The program allows the use of multiple template crystal structures as an input and can create multiple homologous models as an output. We used the highest-resolution (1.2-to 2.4-Å) crystal structures of HIV-1 (18), HIV-2 (33), EIAV (13), FIV (14), and RSV (47) 4 Å], respectively) and generated three simultaneous models for each protease. RSV protease structure was used to interpret the AMV protease results: AMV and RSV proteases differ in only two residues, which are not expected to be involved in the enzyme-substrate interactions (34).…”
Section: Retroviral Proteasesmentioning
confidence: 99%
“…Inhibitors of aspartic proteases have been designed for treatment of AIDS, hypertension, stroke, inflammation, asthma, osteoporosis, the common cold and arthritis [26,28,41,[60][61][62].…”
Section: Aspartic Protease Inhibitors In the Clinicmentioning
confidence: 99%